PROFIL STRATEGI BELAJAR DAN DAMPAKNYA TERHADAP PENCAPAIAN HASIL BELAJAR BAHASA INDONESIA SISWA SEKOLAH DASAR - Dyah Werdiningsih (Faculty of Languages and Arts, Universitas Negeri Yogyakarta, 2011)
This study aims to investigate the profile of the Indonesian language learning strategies that elementary school students use in terms of types, intercorrelations, and effects on learning outcomes. This was a correlational study. The data were analyzed using the descriptive statistics to obtain the means representing the learning strategies and the inferential statistics consisting of the correlation to find out the intercorrelations of learning strategy categories and the linear regression to find out contributions of learning strategies to learning outcomes. The results show that: (1) the six learning strategies are frequently used with a mean of 3.69, (2) they are significantly interrelated, and (3) they give significant contributions to the language mastery attainment with F 4.552 (p .000).